PENGARUH PENAMBAHAN EKSTRAK JAHE DAN METODE PEMASAKAN TERHADAP KUALITAS ORGANOLEPTIK DAN KADAR AIR TELUR ASIN ITIK - Pitri Septiya Desiati; Dyah Nurul Afiyah (Universitas Islam Kadiri, 2018)
This study aims to determine the effect of cooking method and addition of ginger extract to organoleptic quality and salty egg moisture content. The results of this study are expected to provide information on the effect of cooking method and addition of ginger extract to organoleptic quality and salty egg moisture content. This research was conducted in Baye Kayen Kidul Kediri Village on March 10 - March 20, 2018. The material used in this research is duck egg less than 5 days old totaled 192 items. The cooking method used in this research is steaming and boiling. Ginger used in this study are red ginger. The research moisture content and organoleptic. The treatment given was L1 with the cooking method steamed for 30 minutes with temperature 60C and L2 with the cooking method boiled for 30 minutes with temperature 60C with ginger dose 0%, 105, 15% and 20%.The result of factorial RAL L1 and L2 gives significant effect (P <0.05) on organoleptic and water content, including: taste, odor salted egg. The conclusion of this research is the results of organoleptic test of salted eggs with ginger extract and cooking method streamed adn boiled gives significant effect. Suggestion from this research to make salted eggs by using a edonic test using steaming cooking method and using ginger extract at a dose of 15% because it can provide good organoleptic quality in terms of taste and odor.